'Mother Nature Had Been Digitalized': Collecting Sounds and Naturalising Interior Soundscapes. Issue 6 (1st November 2020) - Hui, Alexandra
Abstract : In the late 1960s, composers and sound engineers began to regularly step out of the recording studio. The street sounds and nature sounds they collected, processed, and produced as records and radio broadcasts were intended to be functional. That is, for individuals such as Tony Schwartz, Irv Teibel, and members of the World Soundscape Project, the compositions were expected to generate specific effects, from socio-political change, to altered moods, to environmental conservation. Though part of the sonic counterculture, their efforts also fit into an arc of functional background music from Edison, to industrial music systems, to Muzak, to foreground music and, presently, streaming audio. Using the methodological framework of the history of the field sciences that focuses on collecting practices as well as storage, analysis, and the importance of the specificity of location (versus the universality of the laboratory or studio), recorded musical and non-musical sounds came to be understood as mobile; collectible. I trace the implications of these mobile recorded sound for the way people understood their environment and, in turn, naturalised their built spaces.